A interação pelo sopro. Caso Ar.Cade: avaliação da usabilidade de controlo de patologias respiratórias - Ana Rita Aleixo Pires de Lima (2017)
The mobile platform Ar.Cade is an innovative mobile app that intends to control Asthma in children outside the hospital environment. The main goal of it's daily use is to avoid acute respiratory situations in order to reduce the time children spend in emergency centres. As a "home-made spirometry", this app's purpose is to inform parents, teach children and monitor their respiratory development through blow activated games. It is important to asses and ensure usability of this interaction paradigm since there is still no diverse sample of this type of apps. The lack of knowledge in this area leads to the need of conducting field work and observation in order to establish rules in creating this type of content. By means of three observational moments and usability testing sessions, we have evaluated two Ar.Cade prototypes and have worked on updates in order to maximize the efficiency and effectiveness of this app with the resolution of creating an innovative platform that helps both children and their parents in understanding how to deal with a pathology that is not disabling neither should determine limitations in the life of those who have it.